Detection rate of 18F-Fluorethylcholine-PET/CT in relation to PSA value in PCA patients referred with biochemical relapse - Takesh, Mustafa; Odat Allh, Khaldoun; Zechmann, Christian (Contrast media & molecular imaging, 2020)
Attempts to predict the likelihood of positive morphological imaging related with PSA value in patients referred with biochemical recurrence were the focus of many studies. Using nuclear medicine modalities, numerous studies likewise had been performed for the same purpose, however mostly using C-11-labeled choline. For this purpose, we selected 193 prostate cancer patients from our database between 2006 and 2010. They had been referred to our department to undergo 18F-fluorethylcholine (FECH)-PET/CT due to biochemical recurrence after potentially curative procedures. As a result, in 84 out of 193 patients, 18F-FECH-PET demonstrated positive findings with an overall detection rate of 44%. Statistically, there was a significant difference in PSA values in positive findings vs. negative findings (), and there was a linear correlation between the detection rate and PSA value (r = 0.91). Moreover, there was a relation between initial therapy and recurrence type. So, the local relapse was the most frequent recurrence (>70%) after radiation therapy alone. By contrast, patients after radical prostatectomy followed by salvage radiotherapy showed a low likelihood of local recurrence. In conclusion, PSA value was confirmed to have a determinant role in 18F-FECH-PET outcome. Moreover, there was a link between recurrence type and initial therapy, which—if prospectively confirmed—may play a guiding role in selecting the appropriate diagnostic methods.
Gesehen am 29.09.2020
Im Titel ist "F" hochgestellt bei 18F-Fluorethylchloinge-PET/CT